Titanium - ceramic restoration: How to improve the binding between titanium and ceramic - Harry Laksono (Universitas Airlangga, 2011)
Background: Titanium alloys has been used as an alternative to nickel-chromium alloys for metal-ceramic restorations because of its good biocompatibility and mechanical properties. This indicated that it was possible to design coping according to standards established for metal-ceramics. However, titanium is chemically reacting strongly with gaseous elements which causes problems when ceramics are fused to titanium. Purpose: To provide information about improving the bonding between titanium and ceramic. Review: Titanium has two crystal modifications, the close-packed hexagonal (α) structure, up to 880° C, and above this temperature the bodycentered cubic (β) structure. The principal problems is the extensive dissolution of oxygen resulting in thick, oxygen-rich titanium layers called α-case that harms the bonding of ceramic to titanium and the great mismatch in the coefficient of thermal expansion of conventional ultra-low fusing ceramic. Methods have been developed for fusing ceramic to titanium like processing methods, the used of ultra-low fusing titanium ceramic, bonding agent, and protocol for ceramic bonding to titanium. Conclusion: Titanium and titanium alloys, based on their physical and chemical properties suitable for titanium-ceramic restorations, but careful selection of processing methods, ceramic materials, laboratory skill and strict protocol for ceramic bonding to titanium are necessary to improve the bonding between titanium and ceramic. Latar Belakang: Logam campur titanium telah dipakai sebagai salah satu bahan alternatif untuk logam nikel-krom pada pembuatan restorasi keramik taut logam karena mempunyai biokompatibilitas dan sifat mekanik yang baik.